Isolation and characterization of two novel bacteriophages against carbapenem-resistant Klebsiella pneumoniae - Senhaji-Kacha, Abrar; Bernabéu-Gimeno, Mireia; Domingo-Calap, Pilar; Aguilera-Correa, John Jairo; Seoane-Blanco, Mateo; Otaegi-Ugartemendia, Sara; van Raaij, Mark J.; Esteban, Jaime; García-Quintanilla, Meritxell (Frontiers in Cellular and Infection Microbiology, 2024)
The increase of antibiotic-resistant bacteria has become a global health emergency and the need to explore alternative therapeutic options arises. Phage therapy uses bacteriophages to target specific bacterial strains. Phages are highly specific and can target resistant bacteria. Currently, research in this regard is focused on ensuring reliability and safety to bring this tool into clinical practice. The first step is to conduct comprehensive preclinical research. In this work, we present two novel bacteriophages vB_Kpn_F13 and vB_Kpn_F14 isolated against clinical carbapenem-resistant Klebsiella pneumoniae strains obtained from hospital sewage. Multiple studies in vitro were conducted, such as sequencing, electron microscopy, stability, host range infectivity, planktonic effect and biofilm inhibition in order to discover their ability to be used against carbapenem-resistant K. pneumoniae pathogens causing difficult-to-treat infections.